Mitigasi Risiko Komputasi Awan - joni joni; Teguh prasandy; Imanuel Revelino Murmanto (ULTIMA InfoSys, 2019)
The business world is developing very dynamically along with the development of information technology (IT). The technology or system that is currently invested will become obsolete in the next few years. Companies are starting to consider using cloud computing to keep up with the latest technology and reduce the complexity of managing IT experts, so they can focus on their main business processes. But when it comes to implementing cloud computing, there are risks that cannot be avoided. The purpose of this paper is to analyze the risks of using cloud computing, so that it can provide guidelines and guidelines for companies that want to switch to cloud computing services. The method used in writing this paper uses a literature study approach through tracing journals, textbooks, and the internet. Based on these searches it is known that cloud computing can be adopted by companies that want to get agility and flexibility when businesses grow rapidly, but must still pay attention to corporate governance, risk management, and compliance with regulations